Antioxidant and antiaging properties of Diplazium esculentum / Ili Karmila Norazli - Norazli, Ili Karmila (2023)
Diplazium esculentum, a wild edible fern group, has been reported to have several medicinal benefits, but its cosmeceutical potential in terms of antiaging remains unknown. This study investigated the methanol and petroleum ether extracts of D. esculentum for their potential antioxidant and antiaging properties. The spectrophotometric method was used to evaluate antioxidant activities determined by DPPH (1,1-diphenyl-2-pricrylhydrazyl) free radical scavenging assay at 3, 2, 0.4, 0.008, 0.0016 ug/ml concentration, and to assess antiaging based on tyrosinase inhibition assay at a fixed concentration, 0.5 mg/ml. The percentage yield of D. esculentum in methanol was 4.337%, while it was 1.032% in petroleum ether. Methanol and petroleum ether extract had IC50 values of 0.505 mg/ml and 0.347 mg/ml, respectively. D. esculentum in petroleum ether extract had a higher tyrosinase inhibition activity with 76.659% ± 4.375 than in methanol extract with 51.767% ± 4.957. These findings indicated that D. esculentum has potent antioxidant and antiaging properties that could be used to develop safe and cost-effective antiaging solutions.